Characteristics and Long-Term Outcomes of Pregnancy-Onset Inflammatory Bowel Disease: A Case-Control Study. Issue 4 (19th May 2020) - Yu, Amy; Friedman, Sonia; Ananthakrishnan, Ashwin N
Abstract: Background: Inflammatory bowel disease (IBD) frequently affects women during their reproductive years. Although the impact of pregnancy in patients with established IBD has been widely studied, the characteristics and outcomes of patients who develop a new diagnosis of IBD during pregnancy or the postpartum year ("pregnancy-onset") is not well characterized. Methods: We identified all patients with pregnancy-onset IBD between 2006 and 2018 at 2 major academic referral centers. Patient and disease characteristics were abstracted and compared to those of control patients with IBD not diagnosed during pregnancy or postpartum. Diagnostic and therapeutic interventions were noted, as were long-term outcomes including disease treatment course, hospitalizations, and surgery. Results: We identified 50 patients with pregnancy-onset IBD and 100 control patients matched for year of diagnosis. The mean age of diagnosis and duration of follow-up was similar among both patients and control patients (aged 30.4 vs 28.5 years). Among patients with pregnancy-onset disease, 30% noted symptom onset in the first trimester, 22% in the second, 24% in the third, and 24% in the postpartum year. Patients with pregnancy-onset IBD were more likely to be diagnosed with ulcerative colitis compared with control patients (76% vs 56%; P = 0.02). On multivariable analysis, pregnancy onset-disease had a 4-fold increase in the risk of hospitalization (28% vs 13%; adjusted odds ratio 4.18; 95% confidence interval, 1.26-13.91). This increased risk persisted even after excluding any index hospitalizations during pregnancy. Conclusions: Patients with pregnancy-onset IBD more commonly develop ulcerative colitis and have a higher risk of disease-related hospitalizations.